Reaction kinetics and the development of catalytic processes : proceedings of the international symposium, Brugge, Belgium, April 19-21, 1999 - Froment, Gilbert F.; Waugh, K. C. (Studies in surface science and catalysis, 1999)
The symposium "Reaction Kinetics and the Development of Catalytic Processes" is the continuation of the very successful International Symposium "Dynamics of Surfaces and Reaction Kinetics in Heterogeneous Catalysis", held in September 1997 in Antwerp, Belgium. These proceedings contain a unique series of top level plenary lectures mainly focused on & bull; the dynamics of catalytic surfaces & bull; the interaction of the reacting molecules with the solid catalyst & bull; the elementary steps of reaction pathways and molecular kinetics. Surface science techniques, molecular modeling, transient kinetic studies, sophisticated and specific reactors are included to a growing extent in the kinetic modeling and the development of catalytic processes. How this is practiced today and how it will evolve in the coming years, and what benefit can be expected for a more fundamentally based approach is the aim of the symposium.